The in-vitro antimicrobial activity of some medicinal plants against β-lactam-resistant bacteria - Joseph Gangoue-Pieboji (Journal of Infection in Developing Countries, 2009)
Background: In effort to identify novel bacterial agents, this study was initiated to evaluate the antimicrobial properties of 17 crude extracts from 12 medicinal plants against beta-lactam-resistant bacteria.